How do prospective parents prefer to receive information about prenatal screening and diagnostic testing?. (25th September 2014) - Willis, A. M.; Smith, S. K.; Meiser, B.; Muller, C.; Lewis, S.; Halliday, J.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Women prefer to receive information about prenatal testing options face‐to‐face from a health professional. Increasing numbers of people are accessing health‐related information online. What does this study add? In spite of increased online access of health information, both women and partners still prefer to receive information about prenatal testing options face‐to‐face. High rates of information seeking were observed among pregnant women and partners, despite seemingly high satisfaction with information provided.